2010
DOI: 10.1088/0964-1726/19/3/035015
|View full text |Cite
|
Sign up to set email alerts
|

A PMMA coated PMN–PT single crystal resonator for sensing chemical agents

Abstract: A highly sensitive lead magnesium niobate-lead titanate (PMN-PT) single crystal resonator coated with a thin film of polymethylmethacrylate (PMMA) useful for detecting chemical agents such as acetone, methanol, and isopropyl alcohol (IPA) is presented. Swelling of the cured PMMA polymer layer in the presence of acetone, methanol, and isopropyl alcohol vapors is sensed as a mass change transduced to an electrical signal by the PMN-PT thickness-shear mode (TSM) sensor. Frequency change in the PMN-PT sensor is de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 49 publications
(64 reference statements)
0
9
0
Order By: Relevance
“…The fabricated sensor prototypes were tested with different chemical agents, and the frequency shift was compared with the conventional QCM sensor combined with PMMA sensing layer. The experiment results showed that PMMA coated PMN-PT exhibited sensitivity more than 6800 times higher to IPA, acetone, and methanol vapors than that of the PMMA coated QCM [120]. However, the high temperature sensitivity and poor stability of the PMN-PT sensors compared to the QCM sensors were mentioned as problems to solve.…”
Section: Pmma-pmn-pt Sensormentioning
confidence: 98%
See 1 more Smart Citation
“…The fabricated sensor prototypes were tested with different chemical agents, and the frequency shift was compared with the conventional QCM sensor combined with PMMA sensing layer. The experiment results showed that PMMA coated PMN-PT exhibited sensitivity more than 6800 times higher to IPA, acetone, and methanol vapors than that of the PMMA coated QCM [120]. However, the high temperature sensitivity and poor stability of the PMN-PT sensors compared to the QCM sensors were mentioned as problems to solve.…”
Section: Pmma-pmn-pt Sensormentioning
confidence: 98%
“…Recently, Frank et al [120] reported more increased sensitivity of PMN-PT bio-chemical sensors using a polymethylmethacrylate (PMMA) film. They demonstrated that PMMA coating on a PMN-PT single crystal resonator is useful for detecting chemical agents such as acetone, methanol, and isopropyl alcohol (IPA) vapors.…”
Section: Pmma-pmn-pt Sensormentioning
confidence: 99%
“…Several groups have investigated the possibility of using metals and metal oxides as breath acetone sensors, with some success. [4][5][6][7][8][9][10][11][12][13][14][15][16][17] There have also been several studies that involved polymeric sensing materials and sensing arrays (including these references [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] ), but there is still room for improvement. Polymeric sensing materials typically provide better selectivity than metals and metal oxides and have the added advantage of lower cost and customization (tailorability).…”
mentioning
confidence: 99%
“…Water vapour, as well as other polar molecule vapours, were assessed for binding to calcein thin films and QCM was used alongside surface plasmon resonance and visible spectroscopy to find that calcein films were highly sensitive compared to similar surfaces (Kruglenko et al ., ). The complementary technique of using a single crystal resonator based on lead magnesium niobate and lead titanate coated with polymethylmethacrylate was used to detect acetone, methanol, and isopropyl alcohol vapours with sensitivities reportedly 6,000 times higher than corresponding QCM sensors (Frank et al ., ).…”
Section: Small Molecule Interactionsmentioning
confidence: 97%